2021
DOI: 10.1088/1755-1315/904/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Germination and Seedling Parameters of Wheat as Affected by Storage Conditions

Abstract: A storage experiment was carried out from 27th April to 27thDecember, 2019 to study the effect of storage conditions i.e. methods (open air, under sunshade and in stores), packages type (normal, gunny, polyethylene and metal containers) and periods of seeds fumigation with phosphine (15, 30 and 45 days) on germination and seedling parameters of wheat. The experiment was arranged in a factorial experiment in randomized complete block design (R.C.B.D.) with four replications. Stored wheat seeds under sunshade pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This is to be logical since the same trend was recorded with regard to roots and shoot length. These results are in harmony with those reported by Seadh et al (2021).…”
Section: Seedlings Dry Weight (G)supporting
confidence: 93%
See 1 more Smart Citation
“…This is to be logical since the same trend was recorded with regard to roots and shoot length. These results are in harmony with those reported by Seadh et al (2021).…”
Section: Seedlings Dry Weight (G)supporting
confidence: 93%
“…In addition, Badawi et al (2017) revealed that the high germination percentage of wheat grains was obtained from grains that were treated with phosphine at the rate of 8 ppm. Furthermore, Seadh et al (2021) stated that the highest final germination percentage, shoot and root length, and seedlings dry weight in addition to the lowest, and speed germination index were recorded with phosphine fumigation at the rate of 3 tablets m-3 after 15 days from beginning the storage. Moreover, Kandil et al (2022) revealed that phosphine fumigation of storage wheat grains with five tablets m-3 significantly increased final germination percentage, root length, shoot length, and seedling dry weight.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Seadh et al. [ 35 ], reported that the interaction effect of storage periods and materials did not have significant influence on speed of wheat germination. The result of this study showed that seeds from the PPBFC and PPBTX had showed better germination speed and there is no statistical difference between seeds from PPBFC and PPBTX in their germination speed.…”
Section: Resultsmentioning
confidence: 99%
“…Germination is the prime important property of a seed and it indicates the viability [ 31 ]. In this study it was understand that, storage materials used were showed effect on emmer wheat seed germination capacity during the studied storage duration [ 35 ]. The overall germination rate of seeds was around 98 percent at the onset of trial.…”
Section: Resultsmentioning
confidence: 99%
“…The highest seed viability and quality were recorded with fumigated wheat grains with phosphine at eight ppm. Seadh et al (2021) stated that the highest final germination percentage, plumule and radical length, seedling vigor index and seedlings dry weight in addition to the lowest abnormal seedlings percentage, rotten and sold seeds percentages, speed germination index, and germination energy percentage were recorded with phosphine fumigation at the rate of 3 tablets/m after 15 days from beginning the storage.…”
Section: Introductionmentioning
confidence: 99%